Minimally extended left-right symmetric model for dark matter with U(1) portal - M. J. Neves (Journal of High Energy Physics, 2018)
Abstract A minimal extension of the left-right symmetric model for neutrino masses that includes a vector-like singlet fermion dark matter (DM) is presented with the DM connected to the visible sector via a gauged U(1) portal. We discuss the symmetry breaking in this model and calculate the mass and mixings of the extra heavy neutral gauge boson at the TeV scale. The extra gauge boson can decay to both standard model particles as well to dark matter. We calculate the relic density of the singlet fermion dark matter and its direct detection cross section and use these constraints to obtain the allowed parameter range for the new gauge coupling and the dark matter mass.